2023
DOI: 10.3390/nu15020378
|View full text |Cite
|
Sign up to set email alerts
|

Sea Cucumber Derived Triterpenoid Glycoside Frondoside A: A Potential Anti-Bladder Cancer Drug

Abstract: Bladder cancer is a highly recurrent disease and a common cause of cancer-related deaths worldwide. Despite recent developments in diagnosis and therapy, the clinical outcome of bladder cancer remains poor; therefore, novel anti-bladder cancer drugs are urgently needed. Natural bioactive substances extracted from marine organisms such as sea cucumbers, scallops, and sea urchins are believed to have anti-cancer activity with high effectiveness and less toxicity. Frondoside A is a triterpenoid glycoside isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Frondoside A, a sulfated saponin from sea cucumbers, inhibits the PAK1-dependent growth of lung and pancreatic cancer cells ( Nguyen et al, 2017 ). Other saponins found in sea cucumbers, such as holotoxin A1 and holothurin A, display anticancer activity, making them valuable for functional food and nutraceutical applications ( Song et al, 2017 ; Ru et al, 2023 ). A new sulfated saponin from sea cucumber exhibits antiangiogenic and antitumor activities both in vitro and in vivo ( Hossain et al, 2020 ).…”
Section: Sources and Pharmacological Effects Of Saponinsmentioning
confidence: 99%
“…Frondoside A, a sulfated saponin from sea cucumbers, inhibits the PAK1-dependent growth of lung and pancreatic cancer cells ( Nguyen et al, 2017 ). Other saponins found in sea cucumbers, such as holotoxin A1 and holothurin A, display anticancer activity, making them valuable for functional food and nutraceutical applications ( Song et al, 2017 ; Ru et al, 2023 ). A new sulfated saponin from sea cucumber exhibits antiangiogenic and antitumor activities both in vitro and in vivo ( Hossain et al, 2020 ).…”
Section: Sources and Pharmacological Effects Of Saponinsmentioning
confidence: 99%
“…It was demonstrated in the reports of Sajwani [ 15 ] and Al Shemaili and Parekh [ 69 ] that frondoside A has a greater growth inhibitory effect on the pancreatic cancer cell lines AsPC-1 and S2-013 compared with frondoside B and C. Studies have also reported the higher antiangiogenic and antimetastatic effects on the cancer inhibitory effect using tumor-bearing mice than other types of frondosides [ 62 , 63 , 64 ]. Recently, Ru and Chen [ 70 ] investigated the individual anti-bladder cancer effects of both frondoside A and its combination with CpG oligodeoxynucleotide (CpG-ODN) in vitro and in vivo. From the results of the study, it was revealed that frondoside A has a potential anti-bladder cancer activity by inhibiting cell viability and migration, inducing apoptosis, and affecting the cell cycle.…”
Section: Saponins (Triterpene Glycosides) From C Frondosamentioning
confidence: 99%
“…The authors concluded that the blocking of P-glycoprotein activity resulted in decrease of multidrug resistance, and the glycoside and its complex with cholesterol may be potential inhibitors of multidrug resistance in tumor cells. Ru et al (2023) [45] have demonstrated the efficacy of frondoside A (6) against bladder cancer. They have found anti-proliferative, anti-invasive, anti-angiogenic, and potent immunomodulatory effects.…”
Section: Biological Activities Of Triterpene Glycosides From C Frondosamentioning
confidence: 99%